UJI KERENTANAN NYAMUK Aedes aegypti TERHADAP LAMDA SIHALOTRIN DAN SIPERMETRIN TAHUN 2016 - Yulistra Naftali Eka Putra; Koerniasari .; Mamik . (Poltekkes Kemenkes Surabaya, 2016)
Dengue Hemorrhagic Fever (DHF) in Indonesia is an endemic disease with morbidity level tends to increase from year to year and extends to 400 regencies/cities from 474 regencies/cities in Indonesia. This disease even frequently causes Outbreaks (KLB). One of the dengue controls is chemical control. Chemical control by using insecticides is the most popular form of control in the society because it is easy to implement. Insecticides are most commonly used are lambda cyhalothrin and sipermetrin because it is cheap and readily available. The use of the same insecticide for around 2-20 years and improper dosage can cause mosquitoes to become resistant. This study aimed to test the susceptibility of mosquitoes to Lamdacyhalothrin and cypermethrin. This research was experimental and the study design used